Melatonin as an anti-stress signal: effects on an acute stress model and direct actions on interrenal tissue in goldfish - Azpeleta, Clara; Delgado, Mª Jesús; Metz, Juriaan R.; Flik, Gert; de Pedro, Nuria (Frontiers in Endocrinology, 2024)
Melatonin is a key hormone in regulation of circadian rhythms, and involved in many rhythmic functions, such as feeding and locomotor activity. Melatonin reportedly counteracts stress responses in many vertebrates, including fish. However, targets for this action of melatonin and underlying mechanisms remain unknown. This study reports potential anti-stress properties of melatonin in goldfish (Carassius auratus), with a focus on its effect on plasma cortisol, food intake, and locomotor activity, all of them involved in the responses to stress exposure. Indeed, acute injection of melatonin counteracted stress-induced hypercortisolinemia and reduced food intake. The reduced locomotor activity following melatonin treatment suggests a possible sedative role in fish. To assess whether this anti-stress effects of melatonin involve direct actions on interrenal tissue, in vitro cultures of head kidney (containing the interrenal cortisol-producing tissue) were carried out in presence of ACTH, melatonin, and luzindole, an antagonist of melatonin receptors. Melatonin in vitro reduced ACTHstimulated cortisol release, an effect attenuated by luzindole; this suggests the presence of specific melatonin receptors in interrenal tissue. In summary, our data support a role for melatonin as an antistress signal in goldfish, and suggest that the interrenal tissue of teleosts may be a plausible target for melatonin action decreasing cortisol production.